PENGARUH PERSEPSI ATRIBUT PRODUK TERHADAP MINAT BELI KONSUMEN MOBIL MEREK ISUZU ELF STUDI PADA PT. KARYA ZIRANG UTAMA ISUZUSEMARANG - Kristiana, Nela; Wahyudin, Nanang (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2012)
This research aims to find out that do price, brand, and product quality influence consumer’spurchase interest of Isuzu Elf car brand, and also to analyze the most dominant factor in influencingconsumer’s purchase interest of Isuzu Elf car brand in PT. Karya Zirang Utama Semarang. In theresearch, research population refers to all consumers in PT. Karya Zirang Utama Isuzu Semarang.The samples of the research are 44 respondents by using purposive sampling technique.Based on the research’s result, concluded that regression equality is as follow: Y = 0,130 + 0,249 X1+ 0,279 X2 + 0,359 X3 + e. According to statistic data analysis, the indicators in the research arevalid and the variables are reliable. On classic assumption test, free multikolonieritas regressionmodel, heteroskedastisitas is not happened, and it is distributed normally.The sequence is individually from each variable, and the most influential variable is product qualityvariable with regression coefficient 0,359, then brand variable with regression coefficient 0, 279,whereas the lowest influential variable is price with regression coefficient 0,249. The model equalityhas value as F counts 31,348 and with significance level 0,000, where F counts bigger than F table(2, 85) and with smaller significance level than α (0, 05), while value of T table 1,685 because Tcounts > T table then Ho is rejected and Ha is accepted. It shows that variable independent in theresearch influential partially of dependent variable that is purchase interest.Karya Zirang needs to maintain the product quality and able to create new products with betterquality, in order to can compete with another brand of diesel car.